Muhajirs. Remarks on Muslims’ Emigration from the Bulgarian Lands in the Turn of 19th and 20th Century - Popek, Krzysztof (Balcanica Posnaniensia. Acta et studia, 2017)
During the Russo-Turkish War (1877–1878) and the first months after that conflict about 500 thousands Muslims emigrated from Bulgarian lands, 250 thousands died because of hostilities, hunger, diseases and cold. The prewar number of Muslim population of Principality of Bulgaria and Eastern Rumelia decreased by about 50%. After the peace, the emigration of Muslims was still progressing – it is estimated that in 1878–1912 350 thousands Muslims left Bulgarian lands. The paper concentrated on the main causes and effects of that phenomenon: a lack of career possibilities for the Muslim elites, the fear of retaliation for taking part in pogroms during the April Uprising, the so-called Agrarian Revolution, the defeat of rebellions against the new authorities, army recruitment and an inability to adapt to transformations of the Bulgarian society. There are also presented the attitude of Bulgarian authorities to these phenomenon, which had the pivotal meaning for the demographic structure of Bulgarian state: the percent of Muslims declined from 23,5% in 1879\1881 (for Principality of Bulgaria and Eastern Rumelia) to 15% in 1905.